The cancer of the bladder risk assessment score and mortality-survival relationship among patients who have undergone radical cystectomy in the Turkish urooncology association database - Tavukçu, Hasan Hüseyin; Tinay, İlker; İzol, Volkan; Baltacı, Sümer; Teke, Kerem; Süer, Evren; Yücetaş, Uğur; Yazıcı, Sertaç; Akan, Serkan (My University, 2024)
Objective: The Cancer of the Bladder Risk Assessment (COBRA) score is a practical method that can be used to predict survival in patients who have undergone radical cystectomy (RC). We aimed to evaluate COBRA scores in our patient group. Materials and Methods: Patients were classified according to tumor stage and lymph node (TLN) involvement; mortality rates and survival were analyzed according to both the TLN classification and COBRA score from the Turkish Urooncology Association database. The chi-square test and Fisher-Freeman-Halton Exact chi-square test were used to compare qualitative data as well as descriptive statistical methods. Cox regression analysis was used for multivariate analysis. Kaplan- Meier and log-rank tests were used for survival analysis. Results: There was a statistically significant difference between the COBRA scores and survival rates in terms of cancer-specific mortality according to TLN classification (p=0.000; p<0.05). A COBRA score of 6 was associated with a lower mortality rate than a COBRA score of 5. In the Cox regression analysis of cancer-related death, a one-unit increase in the COBRA score increased the cancer-related death rate 1.54-fold [hazard ratio (HR)=1.540; 95% confidence interval (CI)=1.402-1.691] (p<0.05). When the COBRA score was compared to 0, the highest risk was observed for COBRA 5. If the COBRA score was 5, the risk of cancer- related death increased 14.63 times (HR=14.627; 95% CI=7.041-30.385) (p<0.05). If the COBRA score was 6, the risk of cancer-related death increased by 11.54 times (HR=11.547; 95% CI=5.270-25.278) (p<0.05). Conclusion: The COBRA score increased, the prognosis worsened, and our results are consistent with the first validated study.
Keywords: Bladder Cancer; Cystectomy; Prognosis